ZeroBN: Learning Compact Neural Networks For Latency-Critical Edge Systems - Huai, Shuo; Zhang, Lei; Liu, Di; Liu, Weichen; Subramaniam, Ravi (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
Edge devices have been widely adopted to bring deep learning applications onto low power embedded systems, mitigating the privacy and latency issues of accessing cloud servers. The increasingly computational demand of complex neural network models leads to large latency on edge devices with limited resources. Many application scenarios are real-time and have a strict latency constraint, while conventional neural network compression methods are not latency-oriented. In this work, we propose a novel compact neural networks training method to reduce the model latency on latency-critical edge systems. A latency predictor is also introduced to guide and optimize this procedure. Coupled with the latency predictor, our method can guarantee the latency for a compact model by only one training process. The experiment results show that, compared to state-of-the-art model compression methods, our approach can well-fit the 'hard' latency constraint by significantly reducing the latency with a mild accuracy drop. To satisfy a 34ms latency constraint, we compact ResNet-50 with 0.82% of accuracy drop. And for GoogLeNet, we can even increase the accuracy by 0.3%